Implementasi Nilai Kebangsaan Gotong Royong Dalam Konteks Bhinneka Tunggal Ika: Sinergi Pentahelix Anti Korupsi - Amalia Syauket (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2026)
This study aims to analyze the threat posed by online scamming–based human trafficking syndicates operating in Myawaddy, Myanmar, to Indonesia’s national security. The research employs a qualitative descriptive-analytical approach, utilizing primary data from semi-structured interviews with repatriated Indonesian victims and representatives of relevant institutions, as well as secondary data from international organization reports and scholarly literature. The analysis is based on Hank Prunckun’s (2019) Threat Assessment and Vulnerability Assessment framework. The findings indicate a total threat coefficient of 18.0 (high category), driven by the syndicates’ strong desire and expectation to sustain and expand their operations, supported by acute capabilities derived from advanced knowledge and transnational resources. Meanwhile, the total vulnerability score reaches 13 (acute category), influenced by economic pressures, low levels of digital literacy, the normalization of online recruitment practices, and gaps in crossborder oversight. From a national security perspective (Barry Buzan; Law No. 17 of 2011; Wantannas), this threat is classified as a multidimensional non-traditional threat affecting human security, political and diplomatic security, social and economic stability, as well as cybersecurity and information security.